Exploring Ethnopedagogy: Applying Ethnographic Studies in Thematic Learning in Elementary Schools (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This research aims to examine how ethnopedagogy is implemented in thematic learning at MI Ma'arif Setono Jenangan Ponorogo, and analyze the impact of ethnopedagogy on the thematic learning outcomes of students at the institution. By integrating local wisdom into the curriculum, the study seeks to enhance educational quality while preserving cultural heritage. Methodology: This study utilizes a qualitative ethnographic approach, gathering data through interviews, observations, and documentation. The analysis is conducted using domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. These techniques allow for a detailed exploration of how local wisdom is woven into thematic learning. Main Findings: The findings reveal that ethnopedagogy is incorporated into thematic learning by adapting the curriculum to include local cultural elements. Textbook materials are enriched with local wisdom related to values, norms, beliefs, arts, culture, and natural resources. This approach fosters a deeper connection between students and their cultural environment. Ethnopedagogy positively impacts students' thematic learning outcomes, with students from grades 1 to 6 consistently scoring above the Minimum Mastery Criteria. Additionally, ethnopedagogy enhances students' character development, promoting stronger nationalistic attitudes and a sense of responsibility toward preserving local culture. Novelty/Originality of this Study: This study offers a fresh perspective on integrating local cultural values into primary education curricula. By demonstrating how ethnopedagogy can improve both academic performance and cultural awareness, the research provides a model for sustaining local heritage in the face of globalization, contributing to the broader discourse on culturally responsive education.